Rejuvenation by enthalpy relaxation in metallic glasses. (December 2022) - Meng, Y.H.; Zhang, S.Y.; Zhou, W.H.; Yao, J.H.; Liu, S.N.; Lan, S.; Li, Y.
Abstract: Structural relaxation can be induced by annealing and usually leads to embrittlement in metallic glasses (MGs). Here, we show that a relaxed MG obtained by annealing an as-cast MG at a temperature (annealing temperature, T a ) below its fictive temperature can be suitably rejuvenated by a thermal treatment of the relaxed MG at a temperature higher than T a . The effect is driven by enthalpy relaxation, an endothermic reaction upon heating relaxed MG. This rejuvenation lifts the energy state of the relaxed MG towards that of the as-cast MG. Importantly, we found that the plasticity and fracture toughness of the optimally rejuvenated samples exceed those in the as-cast sample, reversing the relaxation-induced embrittlement in the relaxed sample. An analysis of the structural changes shows that the packing density, rather than the ordering of the atomic structure, is responsible for the effects of rejuvenation. The observed rejuvenation may originate from the recovery of loosely packed regions in the MG atomic structure that were densified during annealing. Our findings are significant for tailoring the mechanical properties of MGs. Graphical abstract: Image, graphical abstract